The impact of content marketing strategy via social media platforms on customer experience: an applied study on Med Care Medical Clinic - Al-Suhaimi, Rana Mohammed; Al-Youbi, Layla Abed (Dirasat: Human and Social Sciences, 2026)
Objectives: This study aimed to investigate the extent to which content marketing strategy is implemented across social media platforms at Medcare Medical Clinic, considering its dimensions (relevance, credibility, value, attractiveness, and emotion). It also sought to determine the success of customer experience with its dimensions (sensory experience, emotional experience, cognitive experience, behavioral experience, and social experience) at Medcare Medical Clinic. Furthermore, the study aimed to identify the impact of the content marketing strategy across social media platforms on customer experience at Medcare Medical Clinic by examining the impact of the dimensions of the content marketing strategy across social media platforms. Methods: case study approach was used to identify the effect of applying content marking via social media platforms and effects on customer experience at Med Care Medical Clinic, questionnaire tool was used as the primary data collection instrument to collecting data from a sample of 322 clients. Results: the most important result The study has reached is Medical Clinic implements content marketing strategy to a high degree, and that customer experience there is equally positive. The study also revealed that content marketing strategy has a 60% influence on customer experience at Medcare Medical Clinic. Conclusions: The study found strong evidence of content marketing strategy implementation at Medcare Medical Clinic, with a corresponding positive effect on customer experience. Consequently, a proposed content marketing strategy framework for social media platforms was developed to further optimize customer experience at clinic.